New In Vitro Phenotypic Assay for Epilepsy: Fluorescent Measurement of Synchronized Neuronal Calcium Oscillations - Pacico, Nathalie; Mingorance-Le Meur, Ana (PLOS ONE, 2014)
Research in the epilepsy field is moving from a primary focus on controlling seizures to addressing disease pathophysiology. This requires the adoption of resource- and time-consuming animal models of chronic epilepsy which are no longer able to sustain the testing of even moderate numbers of compounds. Therefore, new in vitro functional assays of epilepsy are needed that are able to provide a medium throughput while still preserving sufficient biological context to allow for the identification of compounds with new modes of action. Here we describe a robust and simple fluorescence-based calcium assay to measure epileptiform network activity using rat primary cortical cultures in a 96-well format. The assay measures synchronized intracellular calcium oscillations occurring in the population of primary neurons and is amenable to medium throughput screening. We have adapted this assay format to the low magnesium and the 4-aminopyridine epilepsy models and confirmed the contribution of voltage-gated ion channels and AMPA, NMDA and GABA receptors to epileptiform activity in both models. We have also evaluated its translatability using a panel of antiepileptic drugs with a variety of modes of action. Given its throughput and translatability, the calcium oscillations assay bridges the gap between simplified target-based screenings and compound testing in animal models of epilepsy. This phenotypic assay also has the potential to be used directly as a functional screen to help identify novel antiepileptic compounds with new modes of action, as well as pathways with previously unknown contribution to disease pathophysiology.